In vitro Plant Production through Apical Meristem Culture of Bitter Gourd (Momordica charantia L.) - Huda, AKMN; Sikdar, B; Sikdar, B (Plant Tissue Culture and Biotechnology, 2008)
The growth of meristem was observed on semisolid MS medium supplemented with 0.05 mg/l Kn + 0.1 mg/l GA3. After three weeks, meristems were transferred to MS supplemented with BA, Kn, IBA, NAA and IAA singly or in combination for shoot elongation and root initiation. Among different treatments for shoot initiation with elongation were obtained in MS supplemented with 1.0 mg/l BA + 0.1 mg/l IBA + 0.3 mg/l GA3. On the other hand good rooting was observed when 0.5 mg/l IBA and 0.1 mg/l NAA were used to fortify MS semisolid medium. Ten weeks old in vitro plantlets were successfully planted in soil through gradual acclimation. Key words: Apical meristem, Bitter gourd, In vitro, Plant production Â DOI = 10.3329/ptcb.v16i1.1103 Plant Tissue Cult. & Biotech. 16(1): 31-36, 2006 (June)